IDENTIFIKASI KOMODITAS PERTANIAN PANGAN, PALAWIJA DAN HORTIKULTURA UNGGULAN DI KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA (Identification of Leading Agricultural Commodities for Food Crops, Secondary Crops and Horticul-ture in West Tompaso District of Minahasa Regency) - Naomi Balirante; Martha M. Sendow; Oktavianus Porajouw (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The purpose of this study was to identify agricultural, food crops and horticultural commodities which are among the leading agricultural commodities in the District of West Tompaso. This research was conducted in November 2019 to June 2020. TheÂ data used are secondary data obtained from the Central Statistics Agency of North Sulawesi Province, Minahasa Regency, West Tompaso District and the Agricultural Counseling Center (BPP), West Tompaso District. The data analysis technique used is quantitative and descriptive analysis methods. Where data is processed using LQ analysis or Location Quotient then described using a table. The results showed that the agricultural commodities included in the District of West Tompaso were sweet potatoes for food, peanuts and kidney beans for crops, and shallots and tomatoes for horticulture.Keywords: leading commodity, regional development, location quotient